"Vaccinations are Safe and Effective": Inoculating Positive HPV Vaccine Attitudes Against Antivaccination Attack Messages. (1st September 2016) - Wong, Norman C. H.
Abstract : This study examined the use of two different inoculation messages to confer resistance to persuasive messages attacking the efficacy and safety of the human papilloma virus (HPV) vaccine. A three-phase experiment was conducted involving 110 participants to determine if young women who held positive attitudes toward the HPV vaccine could be inoculated against counterattitudinal attack messages using both a specific and generalized form of an inoculation message. Results found that inoculation treatments aimed at protecting positive attitudes toward vaccinations in general (i.e., all vaccines are safe and effective) were as effective at thwarting attacks on the HPV vaccine as the use of a more specific inoculation treatment (i.e., the HPV vaccine is safe and effective).